INDIVIDUAL WORK PERFORMANCE OF MILLENNIAL EMPLOYEES IN TERMS OF SERVANT LEADERSHIP PERCEPTION - Jayanagara, Oscar (Universitas Pelita Harapan, 2024)
This research investigates how servant leadership impacts the job performance of millennial staff members at UKRIDA Hospital directly. Additionally, it delves into the traits of servant leadership exhibited by leaders and evaluates the job performance of millennial employees at UKRIDA Hospital. A sample using purposive sampling technic from 174 millennial employees at UKRIDA Hospital was collected. Established measurement tools, including the Servant Leadership Questionnaire (SLQ) and Individual Work Performance Questionnaire (IWPQ), were employed. The characteristics of the participants were analyzed using Statistical Package for Social Science (SPSS). Hypotheses were tested using Partial Least Squares Structural Equation Modeling (PLS-SEM). Servant leadership significantly and positively impacts the individual work performance of millennial employees in the hospital setting. Hospitals should cultivate an environment that embraces all facets of servant leadership to enhance the job performance of millennial employees.